Penerapan Terapi Bermain Mewarnai Gambar Dengan Pasir Warna Terhadap Kecemasan Anak Usia Pra Sekolah - Dewi Damayanti; Madepan Mulia; Maulida Rizki Amalia (Madago Nursing Journal, 2022)
Introduction: Anxiety of preschool children can be caused due to separation, feelings of loss, bodily injury and pain. The impact of this anxiety risks disrupting the child's growth development and the healing process. Efforts to reduce anxiety of preschool children can be done by giving playing therapy coloring pictures with colored sand. Useful Aim: This study aims to determine the anxiety of preschool children who experience hospitalization before and after being given playing therapy coloring pictures with colored sand in Rumah Sakit Ibu dan Anak (RSIA) Restu Bunda Bandar Lampung. Research Methods: The method in this study by giving playing therapy coloring pictures with colored sand for two participants preschool children children who experienced nursing problems due to hospitalization which were reported in the form of case studies. Results: The results obtained were a decrease in signs and symptoms of hallucinations and an increase in the patient's ability to cope with hallucinations. Suggestion: Nurses are expected to provide optimal application of play therapy coloring pictures with color sand to pre-school age children who experience anxiety nursing problems.